PERAN PENYIDIK DALAM PENYIDIKAN TINDAK PIDANA PERDAGANGAN ORANG (STUDI KASUS DI WILAYAH HUKUM POLRES METRO JAKARTA BARAT PERIODE 1 JANUARI 2023 S/D 31 DESEMBER 2023) - Riza Rachman, Dimas; Lumban Gaol, Selamat (YAYASAN PENDIDIKAN DAN PELAYANAN KESEHATAN RAHMAT HUSADA, 2025)
Investigating the crime of human trafficking is a series of actions carried out by investigators looking for and collecting evidence, with this evidence becoming clear about the crime that occurred. This was done to eradicate the crime of human trafficking. In this research, we will discuss the regulation of criminal acts of human trafficking based on national and international criminal law and obstacles for investigators in investigating criminal acts of human trafficking in the jurisdiction of the West Jakarta Metro Police for the period 1 January 2023 to 31 December 2023. The legal research method used is the normative juridical legal research supported by empirical data. Using a statutory approach and a conceptual approach. obtained from primary, secondary and tertiary legal material sources. Regulation of the Crime of Human Trafficking Based on the National Criminal Law currently in force is regulated in Law Number 21 of 2007 concerning the Eradication of Human Trafficking and Investigation of the Criminal Act of Human Trafficking Based on the Indonesian Criminal Law currently in force, regulated in the Republic of Indonesia State Police Regulation Number 6 of 2019 concerning Investigation of Criminal Acts and in the future it will be regulated in Article 455 of Law Number 1 of 2023 concerning the Criminal Code and Regulation of Criminal Acts of Human Trafficking based on International Law, namely the Palermo Protocol, the Convention on the Elimination of All Forms of Discrimination Against Women (Convention on the Elimination of Discrimination Against Women/CEDAW) and Forced Labor Convention Obstacles for Investigators in Investigating Crimes of Human Trafficking in the Legal Area of the West Jakarta Metro Police for the Period 1 January 2023 to 31 December 2023 include Victims Not Wanting to Report, Lack of Human resources for investigators, cooperation between institutions is less than optimal and cooperation between countries is lacking.